Silversmiths for the Inca: The Translation of Documents from the General Language to Spanish in the Late Seventeenth-Century Lima Audiencia - De La Puente Luna, José Carlos (2019)
A 1693 document sheds light on the translation into Castilian of witness testimonies uttered in the lengua general and recorded in writing a century earlier, as part of the activities of the interpreters-general in Lima’s appellate court (audiencia). The case demonstrates the official admission of written Quechua in judicial procedures as late as the closing decades of the seventeenth century. It reinforces the idea that the use of one or more standard varieties of Quechua by litigants and interpreters made the interpretive work of these translators in plurilingual contexts such as the court’s judicial district possible.